Microstructural and electrical behavior of recycled soda lime silica glass doped ZnO-CoO based varistor ceramics - Ismail, Nur Quratul Aini (2020)
The need for green dopant to fabricate a reliable electronic component to protect electrical circuits from overvoltage has gained considerable attention in varistor ceramics field. It is worth to reveal a new potential of recycle Soda Lime Silica (SLS) glass as a dopant electrical enhancer in Cobalt oxide doped Zinc oxide based varistor ceramics. The objectives of the study are; to synthesis ZnO-CoO varistor ceramics at different SLS glass concentration from 0.5 to 2.0 mol% by solid state method sintered at 1100 °C for 2 hours; secondly to study the effect of varied SLS glass concentration using different milling method (wet and dry); and thirdly to study the effect of sintering time varies from 60 to 180 minutes on microstructure and electrical properties of ceramics by dry milling method. The raw materials were weighed to their mol percentage and then subjected to a 24 h ball milled process, powder pre-sintered at 800 °C for 2 h, pressed by 4 tonne pressure to produce pellet form of 10 mm diameter with 1 mm thickness and sintered. The characterization is divided into structural, morphology and electrical measurement. The structural and morphology of varistor ceramics samples were examined with X-ray diffraction (XRD) and Scanning electron microscopy (SEM) with Energy dispersive X-Ray (EDX). The XRD analysis shows the presence of main phase of ZnO on (0 0 2) plane and secondary phases of Zn2SiO4 as reaction between SiO2 in SLS glass with ZnO. The SEM with EDX results shows the microstructure well-formed grains and its boundaries and the presence of all the elements used. It was found that Zn2SiO4 inhibited the grain growth of the ZnO sample thus increase the number of grain boundaries. The density also increases with the increase of doping concentration. This due to the heavier atomic mass of ZnO (65.390) compared to other atomic mass of Si (28.086), Ca (40.078) and Na (22.989). Dry milling shows a good microstructure as the average grain size (D) decrease from 26.12 to 21.60 μm compared to wet milling as the D decrease from 25.01 to 22.46 μm. Moreover, dry milling also exhibits good electrical properties as the nonlinear coefficient α increase from 5.52 to 6.97 compared to wet milling as the nonlinear coefficient increase from 2.82 to 4.38 as increases the SLS glass concentration. Besides, the knee of the J-E curve of dry milling shifted to higher electric field indicating the breakdown voltage (Eb) increase from 120.4 to 261.1 V/cm attributed the decrease of leakage current (JL) from 5.40 to 4.87 μA/cm2. Further study of 2.0 mol% SLS glass doped ZnO-CoO based varistor ceramics was prolonged the sintering time. Samples sintered at 120 minutes shows the smallest grain size of 21.60 μm and largest grain size of 28.80 μm sintered at 180 minutes. Meanwhile, samples sintered at 150 minutes exhibited excellent nonlinear electrical properties since it has high nonlinear coefficient, α = 7.36, lowest in JL = 4.32 μA/cm2 and high in Eb = 278.6 V/cm. In a conclusion, the growth of Zn2SiO4 phase in 2.0 mol% SLS glass doped ZnO-CoO based varistor ceramics by dry milling through solid state method sintered at 1100 °C for 150 minutes produced the best microstructure with grain size of 22.92 μm, and density of 5.45 g/cm3 and the best nonlinear electrical properties with high α = 7.36, lowest JL= 4.32 μA/cm2 and high Eb = 278.6 V/cm.